Effect of interferon on chemiluminescence and hydroxyl radical production in murine macrophages stimulated by PMA. - Ito, M (1985)
Considerably augmented chemiluminescence (CL) occurred when murine peritoneal resident macrophages (MPs), pretreated with murine interferon (MuIFN)-alpha within 24 hr, were stimulated by 4-beta-phorbol, 12-beta-myristate, 13-beta-acetate (PMA). Augmentation of CL generation ceased when incubation in the presence of MuIFN was continued for 48 hr. As 12 hr preincubation with MuIFN procured optimal CL generation, the various reactive oxygen species (OH, O2-., H2O2) were measured at that point. The hydroxyl radical (OH.) level in MuIFN-treated MPs was 19.44 times higher than in MuIFN-untreated MPs. However, the levels of O2-. and H2O2 generation were the same in both MuIFN-treated and untreated MPs. Moreover, by using the inhibitors lipoxygenase and cyclo-oxygenase, we established clearly that CL and OH. generation in MuIFN-treated MPs is due to the lipoxygenase pathway of arachidonic acid metabolism.